Geological and Cultural Heritages of Harput Old City (Elazıg, Eastern Turkiye) - Kaygili, Sibel; Ozkul, Mehmet; Aksoy, Ercan (Springer Heidelberg, 2026)
Harput, which has a long history of approximately 4.000 years in Eastern Anatolia and is on the UNESCO World Heritage Tentative List, has many geological heritage, cultural heritage and intangible cultural heritage values. Owing to its southern edge being controlled by the Elaz & imath;& gbreve; Fault, Harput and its surroundings are located at an elevation with a difference of 400 m compared to the city center of Elaz & imath;& gbreve;. The most prominent geological heritage elements in Harput and its surroundings include Buzluk Cave and & Ouml;lbe Valley, whereas the most well-known cultural heritage element is Harput Castle, and intangible cultural heritage. Examples of intangible cultural heritage elements include conversation meetings and & Ccedil;ayda & ccedil;& imath;ra Folk Dance. Structures such as Arap Baba Tomb and Ankuzu Baba Tomb are the most well-known examples of religious tourism destinations. The tombs containing the graves of people believed to have shown heroism during the conquest of Harput by Arabs and Turks are visited intensively by the local people within the scope of religious tourism. It cannot be said that the geological and cultural heritage elements of Harput are properly protected for transfer to future generations. The aim of this study is to draw attention to the existence and promotion of various heritage elements of Harput and to contribute to their protection and transfer to future generations. It is also clear that these promotion and protection activities are important in terms of geotourism and cultural tourism, and support the economic development of local people.
Keywords: Elaz & imath;& gbreve; Harput castle; Geological heritage; Cultural heritage; Eastern T & uuml;rkiye